Peran Pendidikan dan Penguasaan Teknologi terhadap Permintaan Layanan Finansial di Indonesia - Fahriza, Muhammad; Marta, Joan (Universitas Negeri Padang, 2025)
This study aims to determine the role of education and mastery of technology on the demand for financial services in Indonesia. This study uses secondary data sourced from the 2020 National Socio-Economic Survey (SUSENAS) through the Central Statistics Agency (BPS). The unit of analysis used is households spread across 34 provinces in Indonesia with a sample size of 334,229 households. This study uses a quantitative research design using a data analysis method is logistic regression analysis using the odd ratio equation and using the marginal effect as the average value/change, with hypothesis testing (G test and Z test), using data processing using Stata-14. The results of this study indicate that the role of education has a positive and significant effect on the demand for financial services in Indonesia. mastery of technology has a positive and significant effect on the demand for financial services in Indonesia. The findings of this study are that household demographic and geographic factors, such as gender, age, employment status, per capita expenditure, place of residence, and area of ​​residence, show varying results in their influence on different financial services